Incipient ferralization and weathering indices along a soil chronosequence in Taiwan - Jien, S. H.; Baillie, Ian C.; Huang, W. S.; Chen, Y. Y.; Chiu, C. Y. (Wiley, 2016)
The low hilly topography of Green Island, a volcanic island off southeastern Taiwan, includes an altitudinal sequence of sub-horizontal benches. We examined eight profiles along this sequence, ranging from pale brown loamy coral sand on the lowest bench that fringes the coast at an elevation of about 10 m to deep, intensely red and acid clay on the highest bench at about 240 m. Chemical analyses, differential Fe extractions, thin sections, X-ray diffraction of the clay minerals and indices of pedochemical weathering and strain indicated that soil development progressed by weathering of primary and secondary phyllosilicates through argilluviation in the intermediate stages to the generation of increasing quantities of free Fe. The Fe accumulates as free sesquioxides, which crystallize with age. Taxonomically the soil types progress from sandy coral Arenosol, through Eutric Cambisol, Hypereutric Lixisol and Acrisol to incipient Ferralsol (Udipsamment → Eutrudept → Udalf → Udultisol → Udox in Soil Taxonomy). The profiles are interpreted as a chronosequence, although this is complicated by minor and upwardly diminishing contributions of reef coral to the mainly igneous parent materials. There are also variations in the andesitic-basaltic bedrock, and minor aeolian inputs in the higher and older soil types. Regional eustatic sea-level correlations, 14C dating of carbonates on the two lowest benches and estimates of local tectonic uplift indicate that the incipient Ferralsols on the upper bench might date from about 150 ka. The transition through argilluvial Acrisols to incipient sesquioxide-dominated Ferralsols appears, therefore, to develop within 100–200 ka on Green Island, which is faster than usual.